2019
DOI: 10.15537/smj.2019.8.24449
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of endometrial sampling for the diagnosis of patterns of endometrial pathology in women presenting with abnormal uterine bleeding

Abstract: Objectives: Abnormal uterine bleeding (AUB) is a leading cause of hysterectomies, the cause of which is usually diagnosed with preoperative endometrial sampling. We planned this study to assess the accuracy of diagnosing the histologic patterns of endometrium in the preoperative sample in reference to the final histologic diagnosis in hysterectomy. Methods: We retrospectively reviewed medical charts between January 2011 and December 2015 at a tertiary hospital in Saudi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
6
0
4
Order By: Relevance
“…Preoperative endometrial sampling is an important approach for clinically suspected endometrial lesions, however, the conventional pathological technique is insufficient for risk assessment of EC. Notably, IHC examination can significantly improve the accuracy of diagnosis (7). Several studies report that IHC markers are important for identification of different pathologic subtypes and risk factors of EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative endometrial sampling is an important approach for clinically suspected endometrial lesions, however, the conventional pathological technique is insufficient for risk assessment of EC. Notably, IHC examination can significantly improve the accuracy of diagnosis (7). Several studies report that IHC markers are important for identification of different pathologic subtypes and risk factors of EC.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (5) reported that ADC has the potential to discriminate intermediate-and high-risk stage I EC patients, whereas Lee et al (6) reported that preoperative MRI and histological results can be used for identification of low-risk EC patients. However, results of risk prediction of EC using MRI or IHC alone show significant variations (6)(7)(8)(9). Therefore, it is important to explore the effect of combining preoperative MRI features and IHC markers on the predictive value for high-risk EC.…”
Section: Introductionmentioning
confidence: 99%
“…Следовательно, можно сделать вывод, что гистероскопия является адекватным и надежным инструментом для оценки доброкачественной патологии в полости матки. Визуальных результатов может быть недостаточно, и для повышения точности диагностики может потребоваться направленная биопсия [2,17,18].…”
Section: этиология и патогенез гиперплазии эндометрияunclassified
“…Alterations in uterine bleeding pattern such as abnormal uterine bleeding (AUB) and amenorrhea are among the most common gynecological problems worldwide ( Soleymani et al, 2014 , Al Nemer et al, 2019 ). AUB is a broad term used to denote all forms of uterine bleeding disorders irrespective of frequency, duration, and quantity.…”
Section: Introductionmentioning
confidence: 99%